2018
DOI: 10.1080/02699052.2018.1536282
|View full text |Cite
|
Sign up to set email alerts
|

Blast-induced brain injury in rats leads to transient vestibulomotor deficits and persistent orofacial pain

Abstract: Blast-induced traumatic brain injury (blast-TBI) is associated with vestibulomotor dysfunction, persistent post-traumatic headaches, and post-traumatic stress disorder (PTSD), requiring extensive treatments and reducing quality-of-life. Treatment and prevention of these devastating outcomes requires an understanding of their underlying pathophysiology through studies that take advantage of animal models. Here we report that cranium directed blast-TBI in rats results in signs of pain that last at least 8 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 105 publications
(111 reference statements)
2
16
3
Order By: Relevance
“…Studlack et al previously used beam walk, accelerating rotarod, rearing, open field, elevated plus maze, and light-dark box task tests in bTBI injury model rats to evaluate their motor function and anxiety-related behavior. They observed that the accelerating rotarod test exhibited significant differences between the bTBI and control groups from day 1 to day 14 post injury [45]. We considered that the prolonged symptoms were suitable for evaluating the efficacy of AA2G and confirmed that the accelerating rotarod test exhibited significant differences between the LISW and control groups in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Studlack et al previously used beam walk, accelerating rotarod, rearing, open field, elevated plus maze, and light-dark box task tests in bTBI injury model rats to evaluate their motor function and anxiety-related behavior. They observed that the accelerating rotarod test exhibited significant differences between the bTBI and control groups from day 1 to day 14 post injury [45]. We considered that the prolonged symptoms were suitable for evaluating the efficacy of AA2G and confirmed that the accelerating rotarod test exhibited significant differences between the LISW and control groups in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…We found that multifactorial brain injury induced persistent periorbital and plantar tactile hypersensitivity in mice. This result is consistent with a previous study showing persistent (8 weeks) whisker-pad tactile hypersensitivity after a single direct bullet-less gun-induced TBI in rats estimated at >70 PSI [49]. Interestingly, in a subsequent study, this phenotype was not produced when the TBI was performed in awake animals [50], despite the known protective effect of anesthetics [30].…”
Section: Long-term Vs Transient Hypersensitivity Induced By Tbisupporting
confidence: 92%
“…Limited studies on glial pathology within the thalamus following blast injury have been reported. A study by Studlack et al focused on linking thalamic sensitization to headache and pain following blast injury ( 8 ). Their investigation included characterizing the astrocytic response within the VPM and the posterior thalamus (PO) which are associated with pain transmission.…”
Section: Discussionmentioning
confidence: 99%
“…These neurosensory conditions have become increasingly prevalent in military personnel exposed to blast events and are a common comorbidity of bTBI. Acute vestibulomotor deficits have been noted in 98% of patients diagnosed with bTBI and 72% of these patients report long-term vestibular impairment ( 8 , 9 ). Clinical manifestations of vestibular damage includes motor impairments leading to imbalance, motion intolerance, postural instability and dizziness ( 1 , 10 ).…”
Section: Introductionmentioning
confidence: 99%